PENERAPAN STRATEGI PEMBELAJARAN BERBASIS SAINTIFIK PADA MATA DIKLAT DASAR POLA - Maisa Nurfaizah; Mila Karmila (Universitas Pendidikan Indonesia, 2016)
Exertion to increase education quality continous did according to konventional in spite in innovative, one of method with use the curriculum 2013 or scientific learning strategy. This research purpose for get information about Application Scientific Base Learning Strategy To Training And Education Program For Basic Pattern Subject. Method that use in this research is descriptive method with purposive sample as may as 31 university student that already follow Practice Identification Sphere or it’s usually call by PPL to training and education program for basic pattern subject scientific base. Instrumen information aggregate use in this research is questionnaire for get information from application scientific base learning strategy to training and education program for basic pattern subject that’s observation core ability and knowledge about body proportion, determine position parts of body knowledge, and construction basic pattern top portion knowledge with drapping technique. The result of research indicate that more than half respondent already apply scientific base learning strategy to training and aducation program for basic pattern subject is cover observe activity, ask, collecting information, processing information, and extending information for basic pattern subject.